A generator of large current pulses of short duration; Russian Physics Journal; Vol. 11, № 1 - Bugaev S. P.; Zagulov F. Ya.; Kobal'chuk i. e. [Koval'chuk] B. M.; Mesyats G. A. Gennady Andreyevich (1968, 1968)
В фонде НТБ ТПУ отсутствует